Parametric Study for Production of Dimethyl Ether (DME) As a Fuel from Palm Wastes - Inayat, A. (Elsevier Ltd, 2017)
Dimethyl Ether (DME) has been getting numerous attention as it's potential as the second generation bio-fuel. Traditionally DME is produced from the petroleum based stock which involves two steps of synthesis (methanol synthesis from the syngas and DME synthesis from methanol). DME synthesis via single step is one of the promising methods that has been developed. In Malaysia, due to the abundance of oil palm waste, it is a good candidate to be used as a feedstock for DME production. In this paper, single step process of DME synthesis was simulated and investigated using the Aspen HYSYS. Empty Fruit Bunch (EFB) from palm wastes has been taken as the main feed stock for DME synthesis. Four parameters (temperature, pressure, steam/biomass ratio and oxygen/biomass ratio) have been studied on the H2/CO ratio and DME yield. The results showed that optimum H2/CO ratio of 1.0 has been obtained when having an oxygen to biomass ratio (O/B) of 0.37 and steam to biomass ratio (S/B) of 0.23. The increment in the steam to biomass ratio increased the production of DME while the increment in oxygen to biomass ratio will cause reduction in DME production. © 2017 The Authors.